Been there, done that? Effects of centrality-to-lifestyle and experience use history on angling tourists' loyalty to a Swedish salmon fishery. (September 2022) - van den Heuvel, Lotte; Blicharska, Malgorzata; Stensland, Stian; Rönnbäck, Patrik
Abstract: The incorporation of theories and methods from tourism research in recreational fisheries research is not common practice, despite many parallels between the two research fields. Adopting a tourism perspective could contribute to our understanding of angling tourists' attitudes and preferences and help identify the factors affecting the recruitment and retention of anglers. The concept of destination loyalty reflects a tourist's intention to revisit or recommend a destination, and provides a suitable avenue for studying (repeated) visits to a fishing destination. This study assessed the destination loyalty of angling tourists targeting Atlantic salmon ( Salmo salar L.) and sea trout ( Salmo trutta L.) at the Mörrum river in southern Sweden. A structural equation model validated positive relationships between the psychological dimensions of destination image, satisfaction, place attachment and destination loyalty. In addition, centrality of the angling activity to the anglers' life was identified as a precursor of place attachment and subsequent loyalty. Moreover, anglers with a high experience use history for fishing at Mörrum scored higher than other anglers on several of the indicators for image, satisfaction, place attachment and loyalty. These results show how applying a tourism perspective to traditional recreational fisheries research may help to explain angler loyalty to a recreational fishery, which ultimately contributes to the management of visitor numbers and experiences. The measurement model used in this study can inform future studies involving angling destination loyalty and contribute to creating a universal measurement scale for this construct and its antecedents. Finally, this study holds several implications for fishing destination marketing and management in terms of supporting diversification of the visiting angler population and the experiences the destination provides. Management implications: The model presented in this study highlights the importance of destination image in promoting satisfaction, place attachment and ultimately destination loyalty in a fishing destination. Moreover, we discuss how understanding angler heterogeneity may inform selective marketing efforts and promote loyalty in a variety of anglers. Additionally, we suggest how improving catch and non-catch related destination attributes could enhance the quality of the fishing experience as a whole, which improves satisfaction and fosters place attachment. Highlights: Fishing destination loyalty depends on image, satisfaction and place attachment. High-centrality anglers are more likely to attach, which increases their loyalty. Image and satisfaction of Mörrum specialists differ from place-generalists. Destination improvement should focus on the whole experience, not just the fishing.